In silico Analysis Reveals Distribution of Quorum Sensing Genes and Consistent Presence of LuxR Solos in the Pandoraea Species - Chua, Kah-Ooi; See-Too, Wah-Seng; Ee, Robson; Lim, Yan-Lue; Yin, Wai-Fong; Chan, Kok-Gan (Frontiers in Microbiology, 2019)
The most common quorum sensing (QS) system in Gram-negative bacteria consists of signaling molecules called N-acyl-homoserine lactones (AHLs) which are synthesized by an enzyme AHL synthase (LuxI) and detected by a transcriptional regulator (LuxR) that are usually located in close proximity. However, many recent studies have also evidenced the presence of LuxR solos that are LuxR-related proteins in Proteobacteria that are devoid of a cognate LuxI AHL synthase. Pandoraea species are opportunistic pathogens frequently isolated from sputum specimens of cystic fibrosis (CF) patients. We have previously shown that P. pnomenusa strains possess QS activity. In this study, we examined the presence of QS activity in all type strains of Pandoraea species and acquired their complete genome sequences for holistic bioinformatics analyses of QS-related genes. Only 4 out of 9 type strains (P. pnomenusa, P. sputorum, P. oxalativorans and P. vervacti) showed QS activity and C8-HSL was the only AHL detected. A total of 10 canonical luxIs with adjacent luxRs were predicted by bioinformatics from the complete genomes of aforementioned species and publicly available Pandoraea genomes. No orphan luxI was identified in any of the genomes. However, genes for 2 LuxR solos (LuxR2 and LuxR3 solos) were identified in all Pandoraea genomes (except 2 draft genomes with one LuxR solo gene) and P. thiooxydans was the only species that harbored no QS-related activity and genes. Except the canonical LuxR genes, LuxIs and LuxR solos of Pandoraea species were distantly related to the other well-characterized QS genes based on phylogenetic clustering. LuxR2 and LuxR3 solos might represent 2 novel evolutionary branches of LuxR system as they were found exclusively only in the genus. As a few luxR solos were located in close proximity with prophage sequence regions in the genomes, we thus postulated that these luxR solos could be transmitted into genus Pandoraea by transduction process mediated by bacteriophage. The bioinformatics approach developed in this study forms the basis for further characterization of closely related species. Overall, our findings improve the current understanding of QS Pandoraea species which is a potential pharmacological target in battling Pandoraea infections in CF patients.